Reduced Order Model based Optimally Tuned Fractional Order PID controller for Pressurized Water Nuclear Reactor. Issue 4 (2018) - Santhiya, M.; Abraham, Anuj; Pappa, N.; Chitra, M.
Abstract: — In this paper, the reduced model of the Pressurized Water Nuclear Reactor (PWR) is derived based on the point kinetics equations and thermal equilibrium relations. The power level of the nuclear reactor is controlled by adjusting the insertion reactivity of the rod. Several controllers such as Genetic Algorithm based PID controller (GAPID), Fractional Order PID controller (FOPID) and Genetic Algorithm based Fractional Order PID Controller (GAFOPID) are used to control the power level of the PWR type of nuclear reactor. The simulation results depict that the Genetic Algorithm based Fractional Order PID Controller (GAFOPID) shows the satisfactory response than other control techniques.